ADFC Robot: Ashirwad A Low cost much efficient ADFC(Autonomous Dry Floor Clean-up) Robot (International Journal of Engineering and Computer Science, 2017)
Artificial intelligence is reaching local areas like homes, offices, hospitals and other public places at a rapid pace. Robots are stepping forward to do the task of their creators-Human beings. Many organizations are exploring this field of exploration where design, construction, operation and application are equally important. These mechanical beings are programmed to perform various tasks with 100% approximate of efficiency. The paper focuses on the simplified approach to reduce the cost and improved efficiency of the robot so to serve the community to higher extent. Rotation in the brushes and simultaneous mapping of path facilitate for better clean up as compared to the previous cleaners that are associated with high cost but uses static brushes and random path. It eliminates the use of vacuum cleaners as they are expensive. The rotation brushes projected in the front do the needful to collect the mess in the dustbin attached at the bottom of the robot. Steeper motors are used for the mobility of wheels and brushes. Ultrasonic sensor is used to for obstacle detection. Ultrasonic sensor gathers information from the surrounding to assist the robot to react upon. This robot is programmed to reach each and every part of the floor. Its wiping brush rotates to give better results as compares to the static one. Graphical user interface is provided to switch between different speeds modes.